Exploration of the temporal-spatial expression pattern and DNA methylation-related regulation of the duck telomerase reverse transcriptase gene. (7th May 2019) - Yuan, Taoyan; Zhao, Wanqiu; Niu, Yifan; Fu, Yan; Lu, Lizhi; Niu, Dong
ABSTRACT: Telomerase reverse transcriptase (TERT) is a catalytic subunit of telomerase that adds TTAGGG repeats to the 3′-overhang of telomeres. In the present study, we detected that the duck TERT (dTERT) gene was highly expressed in small intestine and kidney, followed by heart, leg muscle, spleen, pancreas, gonad, and liver at neonatal stage. From embryonic to neonatal stage, the highest dTERT mRNA in liver appeared at stage E19 (19 days at embryonic stage), while for the leg muscle the maximum expression occurred at E26. We also measured the relative telomerase activity (RTA) and relative telomere length (RTL) in the examined tissues and found that the changed tendency of RTA and RTL was not very consistent with that of TERT. In silico analysis revealed that there were three CpG islands (S1, S2, and S3) within the 5′ regulatory region of the dTERT gene. Bisulfite sequencing PCR (BSP) assay showed that liver (D7, 7 days after birth) which expressed significantly lower dTERT mRNA had an obviously higher methylation level of S1 compared with small intestine (D7) or liver (E19). Quantitative real-time PCR analysis revealed that the expression of DNA methyltransferase DNMT1 in liver (D7) was significantly higher than that in small intestine (D7) or in liver (E19). In vitro, dTERT expression was upregulated and the methylation status of S1 decreased in both duck embryonic fibroblasts and small intestinal epithelial cells following treatment with the demethylation reagent, 5-aza-2′-deoxycytidine (5-aza-dC), further suggesting that dTERT is epigenetically regulated by DNA methylation. This work lays a solid foundation for further study of TERT function and regulation in avian species.